2017
DOI: 10.1101/182519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection-like biases emerge in population models with recurrent jackpot events

Abstract: Evolutionary dynamics driven out of equilibrium by growth, expansion or adaptation often generate a characteristically skewed distribution of descendant numbers: The earliest, the most advanced or the fittest ancestors have exceptionally large number of descendants, which Luria and Delbrück called "jackpot" events. Here, we show that recurrent jackpot events generate a deterministic bias favoring majority alleles, which is equivalent to an effective frequency-dependent selection (proportional to the log ratio … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For instance, we have seen that once an allele spreads through the fitness distribution and reaches mutation-selection balance, an effective frequency-dependent selection coefficient emerges s eff (f ), (43) This effective selection coefficient arises due to the deleterious mutations that neutral mutations are linked to, and changes with the frequency f of the mutation as high-fitness individuals within the neutral lineage drift to extinction. This is analogous to the fictitious selection coefficient, s fic (f ) = log f 1−f , that emerges in the model analyzed by Hallatschek (2017). The difference in the form of the effective selection coefficient between our results and the Hallatschek (2017) model is large when N se −λ 1, but becomes negligible as N se −λ → 1; it underlies the differences between the site frequency spectra of rapidly adapting or ratcheting .…”
Section: N Sementioning
confidence: 68%
See 2 more Smart Citations
“…For instance, we have seen that once an allele spreads through the fitness distribution and reaches mutation-selection balance, an effective frequency-dependent selection coefficient emerges s eff (f ), (43) This effective selection coefficient arises due to the deleterious mutations that neutral mutations are linked to, and changes with the frequency f of the mutation as high-fitness individuals within the neutral lineage drift to extinction. This is analogous to the fictitious selection coefficient, s fic (f ) = log f 1−f , that emerges in the model analyzed by Hallatschek (2017). The difference in the form of the effective selection coefficient between our results and the Hallatschek (2017) model is large when N se −λ 1, but becomes negligible as N se −λ → 1; it underlies the differences between the site frequency spectra of rapidly adapting or ratcheting .…”
Section: N Sementioning
confidence: 68%
“…This is analogous to the fictitious selection coefficient, s fic (f ) = log f 1−f , that emerges in the model analyzed by Hallatschek (2017). The difference in the form of the effective selection coefficient between our results and the Hallatschek (2017) model is large when N se −λ 1, but becomes negligible as N se −λ → 1; it underlies the differences between the site frequency spectra of rapidly adapting or ratcheting . CC-BY 4.0 International license peer-reviewed) is the author/funder.…”
Section: N Sementioning
confidence: 74%
See 1 more Smart Citation
“…Previous theoretical work has demonstrated that fat‐tailed distributions of descendants with infinite variance can lead to qualitatively different population genetic dynamics (Der et al, ; Eldon & Wakeley, ; Hallatschek, ; Schweinsberg, ). While our experimentally determined distributions are fatter than log‐normal, it is unlikely that the variance diverges with population size for the particular species and conditions we examined.…”
Section: Resultsmentioning
confidence: 99%
“…However, for some animals there is high variance in reproductive success, with a minority of males fathering a large fraction of the children in each generation (Araki, Waples, Ardren, Cooper, & Blouin, ; Hedgecock, ; Hedgecock & Pudovkin, ; Lallias, Taris, Boudry, Bonhomme, & Lapègue, ). Such highly skewed offspring distributions have fundamental implications for how we predict and interpret fluctuations in allele frequencies (Der et al, ; Eldon & Wakeley, ; Hallatschek, ; Hedrick, ; Hoban et al, ; Schweinsberg, ). These implications include dramatic (e.g.…”
Section: Introductionmentioning
confidence: 99%